Dopamine-Zein synergistic coating for PMP hollow fiber membranes with enhanced biocompatibility and performance in MABR - Fangli Zhang; Chenyang Gu; Yinchao Jin; Rizhi Chen; Dan Li; Jun Pan; Zhaohui Wang; Zhaoliang Cui (Desalination, 2026)

Indirubin attenuates DSS-induced colitis in mice and is associated with partial gut microbiota shifts and altered intestinal metabolic profiles - Junzu Shi; Danyang Cui; Li Yu; Dan Zhang; Yang Gong (Food Research International, 2026)

Contrasting impacts of biodegradable and conventional microplastics on heavy metal bioavailability in soils: A multilevel meta-analysis - Xue-Dan Cui; Zheng-Xiao Jiang; Yi-Hao Mei; Ting-Ting He; Xiao Tan; Ai-Jun Lin; Gui-Lan Duan (Environmental Pollution, 2026)

Allelochemicals stimulation (ACS) strategy: Potential for studying allelopathy and discovery of phytotoxins - Dan He; Zhibo Hu; Haishan Cui; Cheng Li; Qiang Wang; Heng Guo; Lan Liu; Jing Li (Phytochemistry, 2026)

HTSTC: Heterogeneous Turn-Aware Spanning Tree Coverage for efficient multi-USV cooperative path planning - Xiaowei Li; Shihao Yin; Jianjian Liu; Dan Zhang; Yaoran Chen; Yuehan Cui; Yan Peng (Ocean Engineering, 2026)

Selective flotation separation of fine cassiterite from quartz using disodium laureth sulfosuccinate as a collector - Dan Huang; Yiqi Cui; Nan Ye (Minerals Engineering, 2026)

Enhanced bio-electrochemical decolorization of azo dye by an rGO/ polyaniline-modified biocathode: Performance improvement and cathodic microbiome reshaping - Tao Hou; Hong-Li Lu; Naif Abdullah Al-Dhabi; Ai-Hong Chen; Wang-Wang Tang; Meng-Yuan Li; Dan Cui (Journal of Environmental Chemical Engineering, 2026)

Microbial mechanisms of sulfamethoxazole biodegradation at bio-anode elucidated by integrated metagenomics and stable-isotope probing - Hongli Lu; Hui Lin; Da Kang; Donglin Wang; Qiaojuan Wang; Jie Mao; Dan Cui; Yaohui Bai; Jiuhui Qu; Yongzhen Peng (Chemical Engineering Journal, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Mitigate dynamic response analysis of submerged floating tunnel (SFT) under wave and impact loads - Xiaolu Cui; Lihua Wang; Bo Huang; Wenlong Luo; Ke Li; Liang Cheng; Dan Zhong (Ocean Engineering, 2026)

Soil organic carbon, soil heterotrophic respiration, and microbial community assembly in response to vegetation restoration in the karst area of Southwest China - Tongqing Su; Geng Lin; Dan Chen; Tingting Cui; Jianbing Zhang; Weiqun Luo; Baoqing Hu (Pedobiologia, 2026)

Plant small molecules steer lipase selectivity and free fatty acid profiles in enzyme-modified cheese revealed by machine learning–guided analysis - Xiao Tan; Huijin Liu; Qingqing Liu; Dan Hu; Junling Cui; Wushuang Bai; Martin Gand; Binglin Li (Food Chemistry, 2026)

Engineering acyclovir-mediated immune and stromal reprogramming to overcome multidrug resistance in tumors - Dan Zhu; Shujie Tian; Ying Cui; Zhixuan Wang; Ziting Zhang; Biqing Bao; Nadezhda Cherdyntseva; Yewei Zhang; Miaomiao Xu; Lixing Weng (Chemical Engineering Journal, 2026)

Opposite effects of garlic essential oil and protein fertilizer on aerial hyphae outbreak of wine-cap mushrooms: Mechanisms involving the redox imbalance and membrane destabilization - Xinran Yin; HongLin An; Xiaoya Zhao; Hui Cui; Lei Yu; Yanan Sun; Weina Li; Demei Meng; Yang Nie; Xia Gao; Dan Zhu; Fansheng Cheng (Postharvest Biology and Technology, 2026)

Coupled vibration characteristics and vibration mitigation of submerged floating tunnel-track-train under wave load - Xiaolu Cui; Lihua Wang; Ke Li; Wenlong Luo; Liang Cheng; Dan Zhong (Ocean Engineering, 2026)

A loofah-based microalgae-bacteria symbiosis drives efficient nutrient removal from low-C/N wastewater: high biomass characterization and mechanism insights - Zhuochao Liu; Meiqi Ren; Han Ji; Hongli Lu; Liming Yang; Dan Cui; Yongzhen Peng (Environmental Research, 2026)

A comprehensive PTM atlas of Dermatophagoides farinae reveals an acylation-dominated landscape of allergens - Dan Zeng; Xinhui Gong; Ying Zhou; Lingli Han; Panpan Han; Cunyin Yuan; Dongmei Zhou; Ximeng Ma; Yubao Cui (Science China Life Sciences, 2026)

Sericin-bioinspired nanoplatform prevents bisphosphonate-related osteonecrosis of the jaw: synergistic mitochondrial modulation and microenvironmental restoration - Zhuoya Cui; Yuanyang Li; Kehong Guo; Hanrui Liao; Zitong Xia; Tao Wang; Rui Cai; Yao Wang; Gang Tao; Dan Zhao (Chemical Engineering Journal, 2026)

New alkaloids from the marine-derived fungus Penicillium sp. SWMU-WZ04-5 and their cytotoxic activity - Sijing Liu; Jinghao Cui; Mengyu Zhang; Ting Chen; Fengjian Lan; Xiujuan Fu; Siwei Chen; Dan Zhang; Ying Zhang; Hui Lei (Phytochemistry Letters, 2026)

Coupled dynamics and resonance mitigation of submerged floating tunnel roadways under transient impact loads in marine environments - Xiaolu Cui; Jing Chen; Bo Huang; Wenlong Luo; Ke Li; Liang Cheng; Dan Zhong; Pupeng Ai; Shixiao Fan (Ocean Engineering, 2026)

Arabinose side-chains play a crucial role in fermentation properties of RG-I enriched citrus pectin - Jiefen Cui; Xiaoxiao Zhang; Dan Liu; Jirong Wang; Yongkai Yuan; Jinkai Zheng (Food Hydrocolloids, 2026)

Zein-based films with γ-cyclodextrin metal organic framework/oregano essential oil for fruit preservation - Zhenbin Liu; Fengbing Yang; Liangbin Hu; Dan Xu; Guoqiang Zhang; Yumei Liao; Min Cui; Hongbo Li; Haizhen Mo (Food Packaging and Shelf Life, 2026)

Potential of supramolecular solvent-based extraction for decontamination of volatile organic compounds in mechanically recycled polyethylene terephthalate - Jinxin Liang; Tianlong Zhang; Can Xu; Jingjing Pan; Huai-Ning Zhong; Qizhi Su; Anqi Cui; Hanke Li; Dan Li; Ben Dong (Food Packaging and Shelf Life, 2026)

Multi-site surface passivation and photothermal coupling for water-stable and efficient Cs3Bi2Br9-based hydrogen evolution - Chun Sun; Zekang Zang; Jiazhi Cui; Jiabao Bai; Zhengtao Qiu; Ruifeng Wang; Yuxin Zhang; Dan Huang; William W. Yu (Chemical Engineering Journal, 2026)

Construction of a predictive model for postoperative subsyndromal delirium in patients undergoing brain tumor surgery - Min Liu; Dan Duan; Wenjing Sun; Qiang Sun; Wenyao Cui (Acta Neurologica Belgica, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

An Innovative Multi-Model Ensemble Strategy for Subgrade Compaction Quality Assessment Incorporating Moisture Content Effects and Underlying Soil Layer Properties - Jianguang Yin; Chengzhi Xiao; Xinzhuang Cui; Huaxin Han; Luqiang Ding; Hancheng Dan (Transportation Geotechnics, 2026)

PAHs formation and distribution: Mechanistic insights from pyrolysis of chlorine-rich waste polyvinyl dichloride - Dan Li; Xuewei Liu; Abdoulaye Boré; Changhao Cui; Zia ur Rahman; Sirong He; Wenchao Ma; Dahai Yan; Li Li; Guanyi Chen (Journal of Hazardous Materials, 2026)

Corrigendum to “Assessing microbial internal drivers of nitrogen–cycle functional potential in lakeside wetlands: insights from random forest modelling and co-occurrence network analyses” [J. Clean. Prod. 541 (2026) 147519] - Dan Li; Baicheng Hu; Pushuang Li; Wenyi Xu; Wenliang Jiang; Zhaoliang Cui; Weiwei Wei; Chunhua Li; Binghui Zheng (Journal of Cleaner Production, 2026)

Sustainable antibiotic degradation in a pH-adaptable heterogeneous electro-Fenton system: Insights into cross-scale mechanism validation - Meiyi Tang; Tao Hou; Hongli Lu; Yutong Xue; Meiqi Ren; Dan Cui (Journal of Environmental Sciences, 2026)

First investigation into occurrence, trophodynamics, and risk implication of polychlorinated naphthalenes and polychlorinated biphenyls in a terrestrial food chain from Tibetan Plateau - Siyuan Xiong; Wenxiao Pan; Duo Bu; Kai Huang; Boyuan Hu; Shuyi Shen; Qiangying Zhang; Zeng Dan; Xiaomei Cui; Yingming Li; Guorui Liu; Qinghua Zhang; et al. (Environmental Pollution, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Identification of a Novel Mitochondrial-Related Gene Signature for BMSCs in Osteoporosis Combining Single-Cell and Bulk Transcriptome Data - Jishi Jiang; Dan Li; Di Cui; Yunpeng Wan; Pinghui Zhou; Xilong Cui; Haiyang Yu (Biochemical Genetics, 2026)

Territorial spatial carbon balance governance from a spatially refined perspective: Incorporating sub-regional differences in spatial driving effects into zoning regulation - Yifei Xu; Mingxiang Wang; Wei Tang; Sinan Li; Wenqi Ai; Wenjing Xu; Dan Xu; Chang Liu; Jiarui Sun; Weixin Cui (Environmental Impact Assessment Review, 2026)

The potential role of bioactive marine polysaccharides applied in the cancer diagnosis and therapy - Shenghao Liu; Chao Geng; Zhijuan Liang; Liping Wang; Longhao Cui; Dan Li; Yuanbin Chen; Ye Liang (Carbohydrate Polymers, 2026)

Effects of water quality and hydrologic factors on fish diversity in subtropical urban river ecosystems - Qiaoyu Cui; Fangbo Qiu; Chao Li; Yiang Wang; Dan Han; Yan Huang (Environmental Biology of Fishes, 2026)

Hexavalent chromium induced autophagy-dependent mTOR expression mediated by upregulation of HMGA2 - Li Li; Meng Dan; Shengnan Li; Xiaojing Cui; Shibo Bao; Shengxiang Luo; Jun Cao (Toxicology, 2026)

Source apportionment and uncertainty assessment of nitrate and phosphate pollution in shallow groundwater in agricultural watersheds based on multi-isotope methods - Qingfei Chen; Chi Wang; Anqiang Chen; Rongyang Cui; Wanli Hu; Bin Fu; Cunzheng Jiang; Xingwei Chen; Dan Zhang (Groundwater for Sustainable Development, 2026)

Advances in CO2 capture and conversion: the role of adsorbent materials - Dan Li; Haijiao Cui; Wanjie Cai; Nini Wen; Guotai Zhang; Xu Zheng (Fuel, 2026)

Production and functional characterization of an extracellular galactoglucan G2 secreted by the Sinorhizobium sp. ACT002 - Heping Sun; Yue Cui; Aocheng Liu; Deyao Meng; Junpeng Hu; Dan Qin; Jing Li (Carbohydrate Polymers, 2026)

Synergistic antibiotic degradation by polydopamine/BiOBr-modified photocathode in self-powered photo-bio-electrochemical system - Mei-Qi Ren; Hong-Li Lu; Zhuo-Chao Liu; Tao Hou; Shuai Wang; Dan Cui; Yong-Zhen Peng (Bioresource Technology, 2026)

Research progress on spike development of wheat - Yi Ding; Ying Zhang; Tengteng Zhang; Dan Zhao; Yufeng Yang; Kaiyue Wang; Ziqi Zheng; Chaoran Wang; Yongpeng Li; Runya Mao; Yifan Ye; Mengxue Li; et al. (Plant Science, 2026)

Association between prenatal PFAS exposure and catch-up growth in children born with adverse outcomes: evidence from a prospective cohort study - Su-Qin Tan; Yan-Xi Li; Shao-Ya Huang; Shen-Pan Li; Qiong Zhang; Cui-Lan Tang; Ying-Chao Ye; Guang-Hui Dong; Jian Chen; Dan Cai; Xiao-Wen Zeng (Journal of Hazardous Materials, 2026)

Assessing microbial internal drivers of nitrogen–cycle functional potential in lakeside wetlands: insights from random forest modelling and co-occurrence network analyses - Dan Li; Baicheng Hu; Pushuang Li; Wenyi Xu; Wenliang Jiang; Zhaoliang Cui; Weiwei Wei; Chunhua Li; Binghui Zheng (Journal of Cleaner Production, 2026)

Targeting mGluR1-Mediated Microglial ER Stress Mitigates Copper-Induced TBI Neuroinflammation - Dan Wang; Jiawei Zhou; Zhulin Zhou; Dayong Cui; Fengkai Liu; Bo Zhang (Molecular Neurobiology, 2026)

Systematic Review and Meta-Analysis on Heavy Metals and Trace Elements in Mild Cognitive Impairment - Yaxin Dong; Lu Ren; TianRan Tang; Xinyi Zhang; Dan Han; Yingyi Luo; Liqiang Wang; Zonghui Cui; Sheng Ji; Jianheng Zheng; Ying Qing (Biological Trace Element Research, 2025)

Dynamic performance of trains in submerged floating tunnels under wave loading - Linzhong Han; Bo Huang; Wenlong Luo; Cheng Cui; Jie Hou; Hao Ding; Ke Li; Liang Cheng; Dan Zhong; Jiawei Zhou (Ocean Engineering, 2025)

Enhancing reservoir parameter prediction workflows via advanced core data augmentation - Xin Luo; Xinghua Ci; Jianmeng Sun; Chengyu Dan; Peng Chi; Ruikang Cui (Marine and Petroleum Geology, 2025)

Functional characterization of two Caspase-1 transcripts that associated with ASC and NLRC3 in apoptosis and inflammatory response in large yellow croaker Larimichthys crocea - Qiu Yu Hu; Kun Huang Han; Qiu Ye Huang; Wen Feng Cui; Qiao Yun Yang; Yi Dan Liu; Shang Qi Zhao; Xian Yuan Zeng; Ying Li; Wen Qi Zha; Yi Lei Wang; Yong Hua Jiang; et al. (Fish & Shellfish Immunology, 2025)

Performance and mechanistic insights into denitrification enhancement by PPy/rGO-modified carbon felt biocathodes - Shuai Wang; Hong-Li Lu; Tong-Yang Feng; Zhuo-Chao Liu; Mei-Qi Ren; Dan Cui; Yong-Zhen Peng (Chemical Engineering Journal, 2025)

BS-D275: A novel locus on the chromosome arm 2DS governing branched spike development in wheat - Yunfeng Qu; Yongkang Ren; Jinghuang Hu; Yi Liu; Dan Qiu; Yahui Li; Qiuhong Wu; Miao He; Qing Guo; Yu Sun; Wenze Yan; Zhaohui Tang; et al. (Theoretical and Applied Genetics, 2025)

The Association of Cadmium Exposure and Anthropometrics in School-Age Children: A Longitudinal Study - Meng Wu; Linhong Li; Tianwenjing Huang; Jieying Gao; Peng Gan; Shudan Liu; Dan Wu; Siyan Ye; Chengpeng Cui; Longjie Li; Ge Yan; Qin Liu (Biological Trace Element Research, 2025)

Effect of Moisture Content on the Evaluation of Subgrade Compaction Quality using Intelligent Compaction Measurement Values - Jianguang Yin; Chengzhi Xiao; Huaxin Han; Luqiang Ding; Xinzhuang Cui; Hancheng Dan (Transportation Geotechnics, 2025)

Safety and recyclability of active polyethylene terephthalate bottles: A comprehensive assessment using non-target screening and visual sensory evaluation - Can Xu; Sheng Chen; Qi-zhi Su; Jinxin Liang; Ying Zeng; Anqi Cui; Hanke Li; Ben Dong; Dan Li; Huai-ning Zhong (Food Chemistry, 2025)

Discovery of two IgM subclasses in Nile tilapia (Oreochromis niloticus) provides insights into IgM evolution in teleost fish - Yuan-Yuan Yao; Chen-Xi Pan; Yu-Dong Hao; Xun Liu; Dan-Dan Chen; Zheng-Wei Cui; Xiang-Yang Zhang; Jian-Min Ye; Yong-An Zhang; Xu-Jie Zhang (Fish & Shellfish Immunology, 2025)

rGO/polypyrrole-modified bioelectrode reshapes microbial communities for enhanced energy-recovering denitrification in carbon-limited wastewater - Yue-Jia Yang; Hong-Li Lu; Naif Abdullah Al-Dhabi; Wang-Wang Tang; Shuai Wang; Dan Cui (Environmental Research, 2025)

Electrocatalytic oxidation of ranitidine using a fluorinated blue titanium dioxide nanotube array electrode - Jianhui Xu; Zhijie Cui; Xin Fu; Dan Li; Yanyan Zeng; Yunfei Zhang; Peng Liu; Xiangteng Mo; Kexin Cao; Zijie Shen; Shangkun Ye (Journal of Environmental Chemical Engineering, 2025)

Vacancy-rich Nd2S3/TiO2 S-scheme heterojunction for boosted photocatalytic tetracycline hydrochloride degradation: Interfacial engineering and mechanism insight - Qiang Wang; Ying Tang; Tiantian Li; Dan Cui; Weixia Yang; Li Zhang; Kezhen Qi; Feng Yu (Journal of Environmental Chemical Engineering, 2025)

Experimental and numerical study on flame instabilities of methanol blended with ammonia cracked gas under CO2 dilution at elevated ambient conditions - Xianrong Wu; Wenchao Zhu; Mingkun Zhang; Xuanrui Zhang; Dan Shen; Zechuan Cui; Xiangyu Meng; Mingshu Bi (Fuel, 2025)

Grass carp reovirus VP6 inhibits IFN production by degrading TBK1 through the autophagy pathway - Xiao Xu; Zhuo-Cong Li; Bao-Jie Cui; Can Zhang; Na Xu; Yang-Yang Wang; Dan-Dan Chen; Long-Feng Lu; Shun Li (Fish & Shellfish Immunology, 2025)

High sensitivity Ru-modified SnO2/SnS2 nanoflowers for rapid detection of H2S gas - Wenjie Zhao; Weidong Quan; Xiaoyang Duan; Ruitian Yan; Weiping Cui; Taolin Yu; Yinsheng Chen; Dan Xu (Chemical Engineering Journal, 2025)

Acid-resistant microporous polyether nanofiltration membrane with high permeability for wastewater treatment - Chuanqi Zhang; Yanjun Zeng; Dan Lu; Yuxin Tao; Zhikan Yao; Saisai Lin; Yunlong Cui; Lin Zhang (Chemical Engineering Journal, 2025)

Three birds with one stone: In-situ etching-constructing nanocubes protective layer toward highly reversible aqueous zinc-iodine batteries - Xin-Yue Wang; Dan Xie; Zhi-Wei Wang; Fang-Yu Tao; Chang Liu; Wan-Yue Diao; Yu-Ying Wu; Cui-Yan Tong; Jing-Ping Zhang (Chemical Engineering Journal, 2025)

The coastal region in southern China is prone to cyanobacteria contamination in residential air conditioning filters - Changliang Nie; Tingfu Li; Xueyun Geng; Dan Li; Runqi Zhang; Jiayu Cui; Xinyue Zhang; Lingyu Li; Yoshizumi Kajii; Lina Wang; Jianmin Chen (Building and Environment, 2025)

Rhizopus arrhizus Causing Scalp Mucormycosis in a Young Type 1 Diabetic Patient - Mao-Hua Chen; Zhen Cai; Wei Cui; Xu-Dan Yang; Dai-Wen Xiao; Li-Xia Zhang; Zhi-Yuan Jiang (Mycopathologia, 2025)

The challenges and progress of CAR-T cell therapy in the treatment of solid tumors - Kai Cui; Wanjun He; Na Huang; Songshan Zhu; Dan Jiang; Weiqiang Yang; Yiwei Zeng; Muhammad Asad Farooq; Guangxian Xu (Molecular and Cellular Biochemistry, 2025)

Measuring effectiveness of arctic shipping emission reduction policies: A system dynamics approach - Dan Wang; Shuangxin Cui; Yuan Zhao (Transportation Research Part D: Transport and Environment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Ligand-functionalized metal-organic framework-based evaporator for synchronous freshwater production and agricultural wastewater remediation - Ziwei Cui; Jianfei Wu; Ranwei Zhang; Ranran Ji; Menglu Yang; Haokang Fang; Qing Huang; Lixing Kang; Dan Tian (Journal of Hazardous Materials, 2025)

Self-powered Ag2Se/SiO2/Si heterojunctions for ultrafast broadband high-sensitivity photodetection - Weipeng Shi; Rui Guo; Gailing Tian; Wenjing Zhang; Yi Chen; Wenyan Wang; Yonghua Wang; Danfeng Cui; Jinglong Wen; Dan Liu; Chenyang Xue (Chemical Engineering Journal, 2025)

Core-sheath-type TiO2@NH2-MIL-125(Ti) nanocone arrays for sensitive photoelectrochemical detection of carcinoembryonic antigen - Mengjia Zhou; Ziyan Cui; Yun Liu; Dan Wang; Yanzhou Li; Junwei Zhao; Wenwu You (Chemical Engineering Journal, 2025)

Construction and optimization of low carbon-to-nitrogen ratio-adapted Chlorococcum-Bacteria symbiosis for energy-efficient wastewater remediation - Ru Yan; Han Ji; Zhuo-Chao Liu; Mei-Qi Ren; Shuai Wang; Li-Ming Yang; Dan Cui (Bioresource Technology, 2025)

Cyprinid herpesvirus 2 (CyHV-2) ORF67 inhibits IFN expression by competitively obstructing STING phosphorylation - Bao-Jie Cui; Can Zhang; Chu-Jing Zhou; Zhuo-Cong Li; Xiao Xu; Yang-Yang Wang; Dan-Dan Chen; Li Zhou; Long-Feng Lu; Shun Li (Fish & Shellfish Immunology, 2025)

Associations of long-term exposure to PM2.5 and its constituents with children renal function: a national retrospective study in China - Siwen Yu; Chunxia Cui; Wei Wu; Lianlong Yu; Yiya Liu; Qijiong Zhu; Zhiqing Chen; Shangfeng Yang; Yi Lin; Jianxiong Hu; Guanhao He; Xiaomei Dong; et al. (Environmental Research, 2025)

Spatiotemporal dissipation, metabolic dynamics and bumblebees’ toxicity risk of the neonicotinoid insecticide thiacloprid in greenhouse conditions - Lu Bai; Shaodong Pan; Yuweng Sun; Yongpan Shan; Xianpeng Song; Dan Wang; Yajie Ma; Hongyan Hu; Xiangliang Ren; Jinjie Cui; Yan Ma; Changcai Wu (Journal of Hazardous Materials, 2025)

Glass transition features of frozen dough regulated by lentinan molecular weight and their correlation with dough structural and rheological properties - Shunqin Li; Wenjie Sui; Jiayi Cui; Ziyi Wan; Jingxin Zhang; Tao Wu; Dan Liu; Min Zhang (Food Hydrocolloids, 2025)

Pressure-tailored phase engineering for giant enhancement of photoelectric effect in the 2D-layered semiconductor CrPS4 - Junming Feng; Mengyao Qi; Hao Song; Meiyan Ye; Marcin Runowski; Ziyang Hu; Like Huang; Min Lian; Xingbin Zhao; Yaqian Dan; Shuailing Ma; Tian Cui (Chemical Engineering Journal, 2025)

Adaptive trajectory tracking control of underactuated ships using parameter prediction based neural network - Zirui Deng; Jianhui Cui; Zhongxian Zhu; Yangwen Dan; Huawei Xie; Yingjun Hu (Ocean Engineering, 2025)

Structural response analysis of different submerged floating tunnel route selection conditions in the complex strait under the action of typhoon Sepat - Cheng Cui; Bo Huang; Minglin Chen; Wenlong Luo; Jianting Zhou; Hao Ding; Ke Li; Liang Cheng; Dan Zhong; Jiawei Zhou (Ocean Engineering, 2025)

Mercury accumulation in urban forest leaves: Dynamics, driving factors, and potential economic value - Yuliang Xiao; Hongjie Zhang; Jing Zong; Xinyu Bai; Kaili Yang; Xuemei Li; Xin Huang; Yufei Hu; Yuting Bao; Abdur Razzaq; Dan Cui; Zhaojun Wang; et al. (Journal of Hazardous Materials, 2025)

Single-well colorimetric sensor array for discrimination and smartphone-assisted detection of catecholamines based on Fe-carbon dots nanozymes - Guang-Ming Bao; Dan-Dan Chen; Yi-Fan Xia; Zhi-Qiang Cai; Shun-Qiang Cui; Xia Wei; Zhen-Chong Dou; Yuan Yuan; Akimana Sandra; Hou-Qun Yuan (Analytica Chimica Acta, 2025)

Shallow groundwater table fluctuations: A driving force for accelerating the migration and transformation of phosphorus in cropland soil - Qingfei Chen; Heng Yang; Rongyang Cui; Wanli Hu; Chi Wang; Anqiang Chen; Dan Zhang (Water Research, 2025)

Impact of particle-attached microbial denitrification on N2O production in an agricultural-urban watershed - Mengdi Yang; Hanjie Yang; Wencai Wang; Huaiyang Fang; Lu Huang; Dan Li; Lingfang Fu; Shiyuan Ding; Xiao-Dong Li; Cong-Qiang Liu; Gangjian Wei; Dongli Li; et al. (Journal of Environmental Management, 2025)

Quaternary glacial history of the Paleo-Daocheng ice cap (southeast Tibetan Plateau) reconstructed from in situ cosmogenic 10Be ages - Zhigang Zhang; Dan Zhao; Chaogang Zheng; Jian Wang; Jiahong Zheng; Haitao Cui; Zhijun Zhao; Xinggong Kong; Xiaobin Xu; Zhiyang Chang; Yiman Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Engineering wood-MOF networks to realize multilevel weak water interactions for highly-efficient solar water-power cogeneration - Haoran Li; Rongcui Fan; Fudong Zhang; Ziwei Cui; Tiantian Wu; Qing Huang; Fangyuan Kang; Yahui Cai; Qichun Zhang; Dan Tian (Chemical Engineering Journal, 2025)

Research on the regulation mechanism of drought tolerance in wheat - Tengteng Zhang; Ying Zhang; Yi Ding; Yufeng Yang; Dan Zhao; Huiqiang Wang; Yifan Ye; Haojia Shi; Bowen Yuan; Zizheng Liang; Yulu Guo; Yue Cui; et al. (Plant Cell Reports, 2025)

Unveiling bisphenol A-degrading bacteria in activated sludge through plating and 13C isotope labeled single-cell Raman spectroscopy - Habasi Patrick Manzi; Dan Qin; Kai Yang; Hongzhe Li; Claude Kiki; Jean Claude Nizeyimana; Li Cui; Qian Sun (Journal of Hazardous Materials, 2025)

Noble metal (Pd, Pt)-functionalized WSe2 monolayer for adsorbing and sensing thermal runaway gases in LIBs: A first-principles investigation - Hao Cui; Hailong Wu; Dan He; Shouxiao Ma (Environmental Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Z-type ZnIn2S4 homojunction for high performance photocatalytic hydrogen evolution - Wenbo Wang; Jie Liu; Mengxia Cui; Xinghua Li; Luyao Niu; Xi Wu; Yuning Chen; Xiaowei Li; Hancheng Zhu; Dan Wang; Changlu Shao (Chemical Engineering Journal, 2025)

Design and Demonstration of an Underwater High-Stability Rapid Cross-Domain Unpowered Vehicle - Zhiyi Yang; Kaiyan Hou; Yu Cui; Lu Liu; Jinglong Wen; Haozhe Zhang; Zujiang Yuan; Dan Liu; Chenyang Xue (Journal of Marine Science and Engineering, 2025)
Unpowered vehicles are designed for subaquatic operation and are capable of operating rapidly cross-domain. This paper presents a refined and optimized design for a high-stability rapid cross-domain unpowered vehicle. The use of a compact, uniquely configured gas generator maximizes the rapidity of the ascent phase, achieving an average underwater speed of more than 3.5 m/s, all without the need for an additional propulsion system. To enhance the stability of the unpowered vehicle during the cross-domain phase, a recoil compensation deceleration device (RCDD) was engineered. This device, which uses a combination of springs and electromagnets, significantly increases both the launch capability and the attitude adjustment capability, by 50%. Furthermore, to facilitate rapid launch in real marine environments and investigate the attitudes before and after crossing domains, a rapid cross-domain launch mechanism is introduced. Through multiple sea trials, the results indicate that the unpowered vehicle can complete the launch process within 4 s under sea state 3 conditions. The unpowered vehicle provides an effective solution for rapid cross-domain operation in complex marine environments.

Fe2+ inhibits spring viraemia of carp virus proliferation via ATG14-dependent autophagy - Zhuo-Cong Li; Can Zhang; Na Xu; Xiao Xu; Ke-Jia Han; Chu-Jing Zhou; Yang-Yang Wang; Bao-Jie Cui; Dan-Dan Chen; Long-Feng Lu; Shun Li (Aquaculture, 2025)

The influence of different flavor peptides on brain perception via scalp electroencephalogram and development of a taste model - Hongbo Li; Xuchao Feng; Zhenbin Liu; Wenting Wang; Lufei Tian; Dan Xu; Bimal Chitrakar; Zhenkun Cui; Liangbin Hu; Haizhen Mo (Food Chemistry, 2025)

Dynamic evolution of volatile compounds during cold storage of sturgeon fillets analyzed by gas chromatography-ion mobility spectrometry and chemometric methods - Jia-hua Yang; Shan Cui; Mei-jun Sun; Kai Liu; Hao Tao; Dan Zhang; Zi-heng Yan; Chun-yu Kang; Chun-qing Zhao (Food Chemistry, 2025)

Modulation of Fe0-FexSy heterostructure by sulfurization constitutes an electron transfer channel for efficient triclosan degradation - Hantong Qie; Xuan Pan; Daibing Hou; Zihan Wang; Xuedan Cui; Aijun Lin; Jun Cui; Wenjie Yang; Dan Zhao (Chemical Engineering Journal, 2025)

Environmental life cycle assessment on the recycling processes of power batteries for new energy vehicles - You Zhou; Xue-Dan Cui; Ai-Jun Lin; Yan Dong; Gui-Lan Duan (Journal of Cleaner Production, 2025)

Waterborne polyurethane with curcumin moieties for rapid responsive warnings and emergency antimicrobial action: Application in crab freshness preservation - Yubin Zhang; Chanchang Yi; Dan Wu; Yuanyuan Cui; Zefeng Wang (Food Chemistry, 2025)

Lymphatic absorption characteristics of eicosapentaenoic acid -enriched phosphoethanolamine plasmalogen and its gastric and intestinal hydrolysates - Dan-Dan Wang; Xiao-Yu Cui; Xiao-Yue Li; Cheng-Cheng Wang; Chang-Hu Xue; Teruyoshi Yanagita; Tian-Tian Zhang; Yu-Ming Wang (Food Chemistry, 2025)

Metalomics Revealed that Changes of Serum Elements were Associated with Oxidative Stress-Induced Inflammation of Cortex in a Mouse Model of Autism - Can Cao; Jian Li; Wenqi Cui; Jiaohua Dai; Zhiyu Guan; Dan Wang; Xiujuan Zhao (Biological Trace Element Research, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

NIR spectroscopy for quality assessment and shelf-life prediction of kiwifruit - Hongbo Li; Linlin Zhu; Na Li; Zhenbin Liu; Liheng Wang; Bimal Chitrakar; Dan Xu; Zhenkun Cui; Yanhua Tang; Liangbin Hu; Haizhen Mo (Postharvest Biology and Technology, 2024)

Metabolic pathway analysis of methane from methanol as substrate in microbial consortium - Chen Zhao; Aman Khan; Zhang Wei; Wang Jinghong; Zhang Fangzheng; Shen Guinan; Hong Yanhua; Wei Dan; Cui Zongjun; Wang Weidong (Bioresource Technology, 2024)

In silico characterization of Rhodotorula toruloides ELO-like elongases and production of very-long-chain fatty acids by expressing Rtelo2, RtKCR, RtHCD, and RtECR through IRES-mediated bicistrons - Ruixin Zhang; Yue Cui; Hongyang Wang; Dan Qin; Jing Li (World Journal of Microbiology and Biotechnology, 2024)

Lipid nanoparticle-mediated base-editing of the Hao1 gene achieves sustainable primary hyperoxaluria type 1 therapy in rats - Dexin Zhang; Rui Zheng; Zhoutong Chen; Liren Wang; Xi Chen; Lei Yang; Yanan Huo; Shuming Yin; Dan Zhang; Jiaxin Huang; Xingang Cui; Dali Li; et al. (Science China Life Sciences, 2024)

Effect of wogonin, an active ingredient of Scutellariae Radix, on fish infected with Aeromonas hydrophila - Jun Cui; Dan Zeng; Peipei Guan; Ning Jiang (Aquaculture International, 2024)

Effect of alfalfa downy mildew (Peronospora aestivalis) infection on the growth and development of Therioaphis trifolii (Homoptera: Aphidiidae) - Lin-bo Xu; Liang-bin Yu; Fang-zheng Yue; Dan-yang Wang; Wen-long Li; Ba-teer Wulan; Yan-wei Cui (Crop Protection, 2024)

Structural characteristics and gelling properties of citrus pectins after chemical and enzymatic modifications: Conformation plays a vital role in Ca2+-induced gelation - Jiefen Cui; Dan Liu; Yuyang Zhang; Mengyu Ma; Mengshan Shang; Cheng Zhao; Xingmiao Lu; Chengying Zhao; Jinkai Zheng (Food Chemistry, 2024)

The impact of different hydrocolloids on gluten-free bazlama bread quality - Pervin Ari Akin; Yolanda Brummer; Iris J. Joye; Namuk Ergün; Fernanda Peyronel; Dan Ramdath; Steve W. Cui (Food Hydrocolloids, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Synergistic optimization of baffles and aeration to improve the Light/Dark cycle of microalgae photobioreactor for enhanced nitrogen removal performance: Computational fluid dynamics and experimental verification - Yuanqi Liu; Zhuochao Liu; Zhensheng Xiong; Yanni Geng; Dan Cui; Spyros G. Pavlostathis; Houxing Chen; Qingchun Luo; Genping Qiu; Qiaohong Dong; Liming Yang; Penghui Shao; et al. (Bioresource Technology, 2024)

Spatiotemporal variation in rice evapotranspiration under the influence of rice expansion: a case study in the Sanjiang Plain, Northeast China - Yuqi Li; Xuhua Hu; Yufeng Luo; Yang Xu; Peng Huang; Dan Yuan; Changhong Song; Yuanlai Cui; Hua Xie (Paddy and Water Environment, 2024)

Prediction of DEDI index for meteorological drought with the VMD-CBiLSTM hybrid model - Tao Su; Dan Liu; Xingyuan Cui; Xianshen Dou; Bo Lei; Xu Cheng; Mengning Yuan; Renjie Chen (Journal of Hydrology, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

Foliar Application of Ca in Alleviation of Atmospheric Fluoride Stress on Leafy Vegetable and Reduction of Potential Dietary Health Risk - Chun-dan Gan; Si-fan Cui; Jin-yan Yang (Water, Air, & Soil Pollution, 2024)

Exploring the potential of biochar for the remediation of microbial communities and element cycling in microplastic-contaminated soil - Changcai Wu; Yajie Ma; Yongpan Shan; Xianpeng Song; Dan Wang; Xiangliang Ren; Hongyan Hu; Jinjie Cui; Yan Ma (Chemosphere, 2024)

A review on micro- and nanoplastics in humans: Implication for their translocation of barriers and potential health effects - Cui-Lan Bai; Dan Wang; Yu-Ling Luan; Si-Nan Huang; Liang-Ying Liu; Ying Guo (Chemosphere, 2024)

Effective or useless? Assessing the impact of park entrance addition policy on green space services from the 15-min city perspective - Qinyu Cui; Lin Tan; Haoran Ma; Xuelin Wei; Shengao Yi; Dan Zhao; Huiyuan Lu; Peiqun Lin (Journal of Cleaner Production, 2024)

Characterization, hazard identification, and risk assessment of volatile organic compounds in Poly(butylene adipate-co-terephthalate)-based food contact articles - Hanke Li; Hongjian Miao; Lichang Chen; Qi-Zhi Su; Zhenwei Liu; Canghao Xie; Jinxin Liang; Siliang Wu; An-Qi Cui; Can Xu; Ben Dong; Dan Li; et al. (Food and Chemical Toxicology, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Newly graphene/polypyrrole (rGO/PPy) modified carbon felt as bio-cathode in bio-electrochemical systems (BESs) achieving complete denitrification - Yue-Jia Yang; Shuai Wang; Da Kang; Xin Lu; Zi-Chang Lu; Zhuo-Chao Liu; Li-Ming Yang; Dan Cui (Environmental Research, 2024)

Correction to: Induction of forkhead box M1 (FoxM1) by EGF through ERK signaling pathway promotes trophoblast cell invasion - Yunpeng Xie; Dan Cui; Linlin Sui; Yuefei Xu; Ningning Zhang; Yanni Ma; Yinghua Li; Ying Kong (Cell and Tissue Research, 2024)

Research advances of in vivo biological fate of food bioactives delivered by colloidal systems - Chengying Zhao; Dan Liu; Liping Feng; Jiefen Cui; Hengjun Du; Yanqi Wang; Hang Xiao; Jinkai Zheng (Critical Reviews in Food Science and Nutrition, 2024)

Chromatographic methods for rapid aflatoxin B1 analysis in food: a review - Yinyin Liu; Dan Liu; Can Li; Shuangshuang Cui; Ziguang Yun; Jian Zhang; Yong Wei; Fengxia Sun (Critical Reviews in Food Science and Nutrition, 2024)

First comprehensive assessment of dietary chlorinated paraffins intake and exposure risk for the rural population of the Tibetan Plateau, China - Wei Zhou; Duo Bu; Kai Huang; Qiangying Zhang; Xiaomei Cui; Zeng Dan; Yinzheng Yang; Yilin Fu; Qianyuan Yang; Yunhe Teng; Jie Fu; Aiqian Zhang; et al. (Science of The Total Environment, 2024)

Piezocatalytically-induced controllable mineralization scaffold with bone-like microenvironment to achieve endogenous bone regeneration - Xi Cui; Lingling Xu; Yizhu Shan; Jiaxuan Li; Jianying Ji; Engui Wang; Baokun Zhang; Xiaozhou Wen; Yuan Bai; Dan Luo; Chunying Chen; Zhou Li (Science Bulletin, 2024)

Zinc-a2-Glycoprotein Acts as a Component of PNN to Protect Hippocampal Neurons from Apoptosis - Kewei Chang; Liyan Lin; Tingting Cui; Hao Zhao; Jiaxin Li; Chang Liu; Dan Gao; Shemin Lu (Molecular Neurobiology, 2024)

Promoted O2 resistant performance of CO selective catalytic reduction via carbon-coated CuCoAl mixed metal oxides - Keke Pan; Yonghua Yao; Dan Cui; Fei Gao; Minmin Liu; Jianming Dan; Bin Dai; Xuhong Guo; Yanwen Zhang; Feng Yu (Journal of Environmental Chemical Engineering, 2024)

Appropriate stoichiometric ratios of dissolved organic carbon and nitrate can trigger a transition in nitrate removal in groundwater around plateau lakes, Southwest China - Rongyang Cui; Anqiang Chen; Wanli Hu; Bin Fu; Gangcai Liu; Dan Zhang (Science of The Total Environment, 2024)

Combined effects of mulch film-derived microplastics and pesticides on soil microbial communities and element cycling - Changcai Wu; Xianpeng Song; Dan Wang; Yajie Ma; Yongpan Shan; Xiangliang Ren; Hongyan Hu; Jinjie Cui; Yan Ma (Journal of Hazardous Materials, 2024)

Experimental study on the flame-dual field overpressure coupling evolution characteristics of LPG/DME blended gas explosion venting - Gang Zhou; Yang Kong; Jianliang Yu; Qi Zhang; Runzhi Li; Dan Wang; Tao Fan; Yangyang Cui; Ziyuan Li (Journal of Cleaner Production, 2024)

Arbuscular mycorrhizal fungi offset NH3 emissions in temperate meadow soil under simulated warming and nitrogen deposition - Nan Cui; Stavros Veresoglou; Yibo Tian; Rui Guo; Lei Zhang; Li Jiang; Furong Kang; Weizhe Yuan; Dan Hou; Lianxuan Shi; Jixun Guo; Mingzhou Sun; et al. (Journal of Environmental Management, 2024)

Clonally derived chicken primordial germ cell lines maintain biological characteristics and proliferative potential in long-term culture - Ying-Jie Niu; Wenjie Ren; Guangzheng Liu; Kai Jin; Dan Zheng; Qisheng Zuo; Yani Zhang; Xiang-Shun Cui; Guohong Chen; Bichun Li (Theriogenology, 2024)

MEIC-global-CO2: A new global CO2 emission inventory with highly-resolved source category and sub-country information - Ruochong Xu; Dan Tong; Qingyang Xiao; Xinying Qin; Cuihong Chen; Liu Yan; Jing Cheng; Can Cui; Hanwen Hu; Wenyu Liu; Xizhe Yan; Huaxuan Wang; et al. (Science China Earth Sciences, 2024)

Recent advance in high-intensity ultrasound modification of blue food protein: Mechanisms, functional properties and structural alterations - Zhihui Yu; Yating Gao; Xinyi Jia; Shuai Cui; Li Ma; Dan Zheng; Xin Li; Long Li; Lixin Zhang; Yisheng Chen (Trends in Food Science & Technology, 2024)

Different long-term fertilization regimes affect soil protists and their top-down control on bacterial and fungal communities in Mollisols - Xiaojing Hu; Haidong Gu; Junjie Liu; Dan Wei; Ping Zhu; Xi'an Cui; Baoku Zhou; Xueli Chen; Jian Jin; Guanghua Wang (Science of The Total Environment, 2024)

Whole-body aging mediates the association between exposure to volatile organic compounds and osteoarthritis among U.S. middle-to-old-aged adults - Hao-long Zhou; Dong-sheng Di; Zhang-bo Cui; Ting-ting Zhou; Ting-ting Yuan; Qian Liu; Jian-li Zhang; Xiao Luo; Dan-yang Ling; Qi Wang (Science of The Total Environment, 2024)

A novel prebiotic enzymatic hydrolysate of citrus pectin during juice processing - Xingmiao Lu; Chengying Zhao; Dan Liu; Mengxiao Hu; Jiefen Cui; Fengzhang Wang; Liang Zeng; Jinkai Zheng (Food Hydrocolloids, 2024)

Estimating Spatiotemporal Fishing Effort of Trawlers with Vessel-Monitoring System Data: A Case Study of the Sea Area of the Bohai Sea and the Yellow Sea, China - Dan Li; Feng Lu; Shuo Xu; Huiyuan Liu; Muhan Xue; Guohui Cui; Zhenhua Ma; Hui Fang; Yu Wang (Journal of Marine Science and Engineering, 2023)
Measuring the distribution of the fishing effort of trawlers is of great significance for describing marine fishery activities, quantifying fishing systems in terms of marine ecological pressure, and revising the regulations of fishing. The purpose of this paper is to develop an efficient learning algorithm to detect the fishing behavior of trawlers to analyze the distribution of fishing effort. The vessel-monitoring system data of more than 4600 trawlers from September 2019 to April 2023 were used for feature extraction. According to the spatiotemporal information provided by the vessel position data, 11-dimensional features were extracted to form the feature vectors. A Slime Mould Algorithm-optimized Light Gradient-Boosting Machine (SMA-LightGBM) algorithm was proposed to classify the feature vectors to recognize fishing behavior. The presented method showed a remarkable generalization ability and high accuracy, sensitivity, specificity, and Matthews correlation coefficient in the test results, with scores of 98.23%, 98.75%, 97.75%, and 0.9646, respectively. Subsequently, the trained model was used to identify the fishing behavior of trawlers belonging to the coastal provinces of the Bohai Sea and the Yellow Sea in the sea area of 117° E~132° E, 26° N~41° N. The fishing effort was calculated and evaluated according to the fishing behavior recognition results. The mean absolute error was 0.3031 kW·h, and the coefficient of determination score was 0.9772. The thermal map of the fishing effort of the trawler was mapped, and the spatiotemporal characteristics were estimated in the region of interest from 2019 to 2023 with a spatial resolution of 18 degree × 18 degree. This method is an efficient way of analyzing the spatiotemporal characteristics of the fishing effort of trawlers. It provides a quantitative basis for the assessment of fishery resources and can inform fishing policies.

Effects of Ulva prolifera Degradation on Growth Performance and Antioxidant Capacity of Japanese Flounder (Paralichthys olivaceus) Family - Yingming Yang; Wenlong Li; Run Wang; Dan Xu; Yadong Chen; Zhongkai Cui; Songlin Chen (Fishes, 2023)
Massive macroalgae blooms, primarily caused by the overgrowth of Ulva prolifera (U. prolifera) in the Yellow Sea of China, pose a severe risk to both marine organisms and the aquaculture industry. This study’s aim was to evaluate the impact of U. prolifera degradation on the growth performance and antioxidant capacity of Japanese flounder (Paralichthys olivaceus) and select some potential Japanese flounder families (labeled 2101–2108, established by crossbreeding) tolerating U. prolifera degradation conditions. Thus, a 60-day U. prolifera exposure experiment was conducted. The results showed that the contents of Na, K, Mg, and Fe elements in the U. prolifera degradation water were significantly increased. The specific growth rate and survival rate of flounder were significantly decreased under the U. prolifera degradation condition, while the 2101 and 2103 flounder families showed a better growth performance compared with the positive control (PC) group. Moreover, the results showed that activities of total antioxidant capacity (T-AOC), transaminases, and alkaline phosphatase (AKP) in serum were significantly decreased, while the 2103 flounder family showed higher activities. Furthermore, U. prolifera degradation significantly increased superoxide dismutase (SOD) activity and glutathione (GSH) content while decreasing catalase (CAT) activity and malondialdehyde (MDA) content in the liver. Specifically, SOD and CAT activities of the 2103 flounder family were higher than the 2101 flounder family and PC group. In addition, the gill SOD and CAT activities of the 2103 flounder family were significantly higher than the PC group. Similarly, the antioxidant-related gene (sod and cat) expressions were synchronously upregulated or downregulated in the liver and gills in response to U. prolifera degradation. These results revealed that U. prolifera degradation decreased the growth performance and influenced the antioxidant capacity of Japanese flounder, while the 2103 flounder family had better advantages in the U. prolifera degradation condition. Therefore, the 2103 flounder family could be regarded as the potential flounder family tolerating U. prolifera degradation. The increased Fe content in the U. prolifera degradation water may be one of the main causes of the physiological alterations observed in Japanese flounder.

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

The protective immunity induced by Trichinella spiralis galectin against larval challenge and the potential of galactomannan as a novel adjuvant - Ru Zhang; Xin Zhuo Zhang; Xin Guo; Lu Lu Han; Bo Ning Wang; Xi Zhang; Ruo Dan Liu; Jing Cui; Zhong Quan Wang (Research in Veterinary Science, 2023)

Effects of Bio-organic Fertilizer on Soil Fertility, Yield, and Quality of Tea - Wenbin Liu; Shiyu Cui; Lintu Wu; Weili Qi; Junhui Chen; Zhengqian Ye; Jiawei Ma; Dan Liu (Journal of Soil Science and Plant Nutrition, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Study on the relationship between primary structure/ spatial conformation and gel properties of pectins from different varieties - Jiefen Cui; Lin Zhang; Jirong Wang; Shaojie Zhao; Cheng Zhao; Dan Liu; Wenxiang Li; Jinkai Zheng (Food Hydrocolloids, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Facile fabrication of hydrophobic covalent organic framework decorated melamine sponge for efficient separation of immiscible oil-water mixture and water-in-oil emulsion - Yaning Xu; Tiantian Wu; Ziwei Cui; Lixing Kang; Jianzhang Li; Yahui Cai; Dan Tian (Journal of Environmental Chemical Engineering, 2023)

Critical Roles of Protein Arginine Methylation in the Central Nervous System - Kewei Chang; Dan Gao; Jidong Yan; Liyan Lin; Tingting Cui; Shemin Lu (Molecular Neurobiology, 2023)

The role of imports in reducing emissions: evidence from Chinese listed companies - Meng Cai; Riming Cui; Dan Li (Environment, Development and Sustainability, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Effects of biochar and inorganic amendments on soil fertility, tea yield, and quality in both Pb–Cd-contaminated and acidified tea plantations - Wenbin Liu; Yanxin Tang; Jiawei Ma; Weiling Zhang; Shiyan Liao; Shiyu Cui; Zhengqian Ye; Dan Liu (Journal of Soils and Sediments, 2023)

Isolation and Identification of a Phosphate-Solubilizing Pantoea dispersa with a Saline–Alkali Tolerance and Analysis of Its Growth-Promoting Effects on Silage Maize Under Saline–Alkali Field Conditions - Ying Cui; Yujie Zhao; Run Cai; Hao Zhou; Jiaxin Chen; Lirong Feng; Changhong Guo; Dan Wang (Current Microbiology, 2023)

Effects of TCPP and TCEP exposure on human corneal epithelial cells: Oxidative damage, cell cycle arrest, and pyroptosis - Zhen-Ning Zhang; Dan-Lei Yang; Hai Liu; Jue Bi; Ya-Bo Bao; Jiao-Yang Ma; Qin-Xiang Zheng; Dao-Lei Cui; Wei Chen; Ping Xiang (Chemosphere, 2023)

Fabrication of modified electrode by reduced graphene oxide (rGO) and polyaniline (PANI) for enhancing azo dye decolorization in bio-electrochemical systems (BESs) - Ai-Hong Chen; Yue-Jia Yang; Shuai Wang; Li-Ming Yang; Xue-Yun Gao; Dan Cui (Environmental Research, 2023)

Diversity, community structure, and quantity of eukaryotic phytoplankton revealed using 18S rRNA and plastid 16S rRNA genes and pigment markers: a case study of the Pearl River Estuary - Shumin Xu; Guihao Li; Cui He; Yi Huang; Dan Yu; Huiwen Deng; Zhuyin Tong; Yichong Wang; Christine Dupuy; Bangqin Huang; Zhuo Shen; Jie Xu; et al. (Marine Life Science & Technology, 2023)
Understanding consistencies and discrepancies in characterizing diversity and quantity of phytoplankton is essential for better modeling ecosystem change. In this study, eukaryotic phytoplankton in the Pearl River Estuary, South China Sea were investigated using nuclear 18S rRNA and plastid 16S or 23S rRNA genes and pigment analysis. It was found that 18S abundance poorly explained the variations in total chlorophyll a (Chl- a ). However, the ratios of log-transformed 18S abundance to Chl- a in the major phytoplankton groups were generally environment dependent, suggesting that the ratio has potential as an indicator of the physiological state of phytoplankton. The richness of 18S-based operational taxonomic units was positively correlated with the richness of 16S-based amplicon sequence variants of the whole phytoplankton community, but insignificant or weak for individual phytoplankton groups. Overall, the 18S based, rather than the 16S based, community structure had a greater similarity to pigment-based estimations. Relative to the pigment data, the proportion of haptophytes in the 18S dataset, and diatoms and cryptophytes in the 16S dataset, were underestimated. This study highlights that 18S metabarcoding tends to reflect biomass-based community organization of eukaryotic phytoplankton. Because there were lower copy numbers of plastid 16S than 18S per genome, metabarcoding of 16S probably approximates cell abundance-based community organization. Changes in biomass organization of the pigment-based community were sensitive to environmental changes. Taken together, multiple methodologies are recommended to be applied to more accurately profile the diversity and community composition of phytoplankton in natural ecosystems.

Contemporary issues in public sector accounting and auditing - Yang Sun; Dan Cui (The Social Science Journal, 2023)

Effect of exogenous Ca on the physiology and growth indicators of pakchoi under foliar and root fluorine stress - Rui Liu; Si-fan Cui; Chun-dan Gan; Jin-yan Yang (Environmental Geochemistry and Health, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Metagenomic strategies uncover the soil bioavailable phosphorus improved by organic fertilization in Mollisols - Xiaojing Hu; Haidong Gu; Junjie Liu; Dan Wei; Ping Zhu; Xi’an Cui; Baoku Zhou; Xueli Chen; Jian Jin; Xiaobing Liu; Guanghua Wang (Agriculture, Ecosystems & Environment, 2023)

Buffered loofah supported Microalgae-Bacteria symbiotic (MBS) system for enhanced nitrogen removal from rare earth element tailings (REEs) wastewater: Performance and functional gene analysis - Yuanqi Liu; Zhuochao Liu; Dan Cui; Liming Yang; Haiyu Wang; Spyros G. Pavlostathis; Yanni Geng; Zhensheng Xiong; Penghui Shao; Xubiao Luo; Shenglian Luo (Chemosphere, 2023)

Nitrogen in soil, manure and sewage has become a major challenge in controlling nitrate pollution in groundwater around plateau lakes, Southwest China - Rongyang Cui; Dan Zhang; Wanli Hu; Xinmei Zhao; Hui Yan; Gangcai Liu; Anqiang Chen (Journal of Hydrology, 2023)

Hybrid bioreactor built-in with fixed bio-carriers for denitrification with low C/N ratio: Hydrodynamic optimization and microbial divergence - Ke-Wen Wang; Wen-Zong Liu; Da Kang; Yu-Xiang Zhang; Dan Cui (Environmental Research, 2023)

Mechanism of sulfur poisoning to Ru-based catalysts in supercritical water gasification of glycerol: From experiment to combined DFT and kinetics studies - Xinyu Cui; Haoran He; Dan Xie; Lixiao Zheng; Xuebin Wang; Zhao Jiang; Donghai Xu; Yang Guo (Chemical Engineering Journal, 2023)

Predicting residual friction angle of lunar regolith based on Chang’e-5 lunar samples - Jiayan Nie; Yifei Cui; Kostas Senetakis; Dan Guo; Yu Wang; Guodong Wang; Peng Feng; Huaiyu He; Xuhang Zhang; Xiaoping Zhang; Cunhui Li; Hu Zheng; et al. (Science Bulletin, 2023)

Assessment of exhaled pathogenic droplet dispersion and indoor-outdoor exposure risk in urban street with naturally-ventilated buildings - Jian Hang; Xia Yang; Cui-Yun Ou; Zhi-Wen Luo; Xiao-Dan Fan; Xue-Lin Zhang; Zhong-Li Gu; Xian-Xiang Li (Building and Environment, 2023)

Shifts in the sources and fates of nitrate in shallow groundwater caused by agricultural intensification intensity: Revealed by hydrochemistry, stable isotopic composition and source contribution - Rongyang Cui; Dan Zhang; Hongyuan Wang; Bin Fu; Hui Yan; Wanli Hu; Gangcai Liu; Anqiang Chen (Agriculture, Ecosystems & Environment, 2023)

Biomimetic cellulose-nanocrystalline-based composite membrane with high flux for efficient purification of oil-in-water emulsions - Jianfei Wu; Ziwei Cui; Yuxuan Su; Yang Yu; Bo Yue; Jundie Hu; Jiafu Qu; Dan Tian; Xianxu Zhan; Jianzhang Li; Yahui Cai (Journal of Hazardous Materials, 2023)

The structure-function relationships of pectins separated from three citrus parts: Flavedo, albedo, and pomace - Lin Zhang; Jiefen Cui; Shaojie Zhao; Dan Liu; Cheng Zhao; Jinkai Zheng (Food Hydrocolloids, 2023)

The real-time detection of acupuncture-induced extracellular ATP mobilization in acupoints and exploration of its role in acupuncture analgesia - Wei-Min Zuo; Yu-Jia Li; Kai-Yu Cui; Dan Shen; Di Zhang; Ya-Wen Zheng; Meng Huang; Yong Wu; Xue-Yong Shen; Li-Na Wang; Guang-Hong Ding (Purinergic Signalling, 2023)

Genome-wide identification, evolution, and expression analysis of carbonic anhydrases genes in soybean (Glycine max) - Li Wang; Jinyu Zhang; Ruiyang Wang; Zhongwen Huang; Ruifan Cui; Hongqing Zhu; Yuming Yang; Dan Zhang (Functional & Integrative Genomics, 2023)

Prediction of phosphorus concentrations in shallow groundwater in intensive agricultural regions based on machine learning - Heng Yang; Panlei Wang; Anqiang Chen; Yuanhang Ye; Qingfei Chen; Rongyang Cui; Dan Zhang (Chemosphere, 2023)

A pilot scale study on the treatment of rare earth tailings (REEs) wastewater with low C/N ratio using microalgae photobioreactor - Haiyu Wang; Zhuochao Liu; Dan Cui; Yuanqi Liu; Liming Yang; Houxing Chen; Genping Qiu; Yanni Geng; Zhensheng Xiong; Penghui Shao; Xubiao Luo (Journal of Environmental Management, 2023)

In-situ activation of CuAl-LDH nanosheets to catalyze bioorthogonal chemistry in vivo in tumor microenvironment for precise chemotherapy and chemodynamic therapy - Sa Wang; Shuqing Yang; Zhuolin Cui; Xueyan Liu; Yu Yang; Tao Wang; Wenjuan Ma; Yubin Zhou; Ruizheng Liang; Dan Yan; Huizhi Chen (Chemical Engineering Journal, 2023)

Vertical distribution of PbI2 nanosheets for robust air-processed perovskite solar cells - Zhenkun Zhu; Jitao Shang; Guanqi Tang; Zhen Wang; Xiaxia Cui; Junjun Jin; Yuan Zhou; Xiang Zhang; Dan Zhang; Xiaowei Liu; Qidong Tai (Chemical Engineering Journal, 2023)

Evaluation of Copper Levels in Dental Calculus of OSF Patients with Chewing Dried Areca-Nut Quids in Hunan Province of Mainland China - Xi-Fan He; Hui Wang; Ye Tian; Te Zhang; Zhi-Peng Qiu; Xiao-Jiao Cui; Jing-Sha Zhou; Xin-Lan Yan; Yi-Wei Wu; Yi-Sha Pan; Yang-Bo Ning; Lin Chen; et al. (Biological Trace Element Research, 2023)

Tracking antibiotic resistance genes in microplastic-contaminated soil - Changcai Wu; Xianpeng Song; Dan Wang; Yajie Ma; Xiangliang Ren; Hongyan Hu; Yongpan Shan; Xiaoyan Ma; Jinjie Cui; Yan Ma (Chemosphere, 2023)

Sublethal effects of imidacloprid and clothianidin on the biological traits of predatory lacewing Chrysopa pallens (Rambur) (Neuroptera: Chrysopidae) - Yue Su; Xiangliang Ren; Hongyan Hu; Xianpeng Song; Xiaoyan Ma; Dan Wang; Yongsheng Yao; Yan Ma; Jinjie Cui (Crop Protection, 2023)

Effects of fish meal replaced by methanotroph bacteria meal (Methylococcus capsulatus) on growth, body composition, antioxidant capacity, amino acids transporters and protein metabolism of turbot juveniles (Scophthalmus maximus L.) - Jichang Zheng; Wencong Zhang; Zhijie Dan; Xiufei Cao; Kun Cui; Si Zhu; Yanwen Zhuang; Kangsen Mai; Qinghui Ai (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

A 3D smart wood membrane with high flux and efficiency for separation of stabilized oil/water emulsions - Jianfei Wu; Ziwei Cui; Yang Yu; He Han; Dan Tian; Jundie Hu; Jiafu Qu; Yahui Cai; Jianlin Luo; Jianzhang Li (Journal of Hazardous Materials, 2023)

In-situ growth of polyoxometalate-based metal-organic frameworks on wood as a promising dual-function filter for effective hazardous dye and iodine capture - Ziwei Cui; Jianfei Wu; Yaning Xu; Tiantian Wu; Haoran Li; Jing Li; Lixing Kang; Yahui Cai; Jianzhang Li; Dan Tian (Chemical Engineering Journal, 2023)

Enhanced ammonia nitrogen removal from actual rare earth element tailings (REEs) wastewater by microalgae-bacteria symbiosis system (MBS): Ratio optimization of microalgae to bacteria and mechanism analysis - Zhuochao Liu; Dan Cui; Yuanqi Liu; Haiyu Wang; Liming Yang; Houxing Chen; Genping Qiu; Zhensheng Xiong; Penghui Shao; Xubiao Luo (Bioresource Technology, 2023)

Pollution Characteristics, Sources, and Health Risk Assessments of Potentially Toxic Elements in Community Garden Soil of Lin’an, Zhejiang, China - Yue Yan; Rongrong Chen; Hexian Jin; Gul Rukh; Ying Wang; Shiyu Cui; Dan Liu (Bulletin of Environmental Contamination and Toxicology, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Assessment of paddy expansion impact on regional climate using WRF model: a case study in Sanjiang Plain, Northeast China - Peng Huang; Dan Li; Hua Xie; Chaoli Liu; Hayat Ullah; Yang Xu; Changhong Song; Chunsheng Dai; Yuanlai Cui; Yufeng Luo (Theoretical and Applied Climatology, 2022)

Degradation mechanism of BPA under VUV irradiation: efficiency contribution and DFT calculations - Ting-Ting Cao; Han Cui; Dan-Dan Zhou; Xin Ren; Chong-Wei Cui (Environmental Science and Pollution Research, 2022)

Resting-state functional connectivity of the sensory/somatomotor network associated with sleep quality: evidence from 202 young male samples - Youling Bai; Jiawen Tan; Xiaoyi Liu; Xiaobing Cui; Dan Li; Huazhan Yin (Brain Imaging and Behavior, 2022)

Clinical evidence of dietary supplementation with sesame on cardiovascular risk factors: An updated meta-analysis of randomized controlled trials - Haohai Huang; Guanghui Zhou; Rong Pu; Yejia Cui; Dan Liao (Critical Reviews in Food Science and Nutrition, 2022)

The Effect of Chitosan Treatment on the Microbial Diversity of Cold-Stored Macrobrachium rosenbergii - Dan Zhou; Haiqi Zhang; Pengcheng Shen; Yanna Cui; Xueping Ye; Dongren Zhou (Journal of Aquatic Food Product Technology, 2022)

Association of white matter volume with sleep quality: a voxel-based morphometry study - Youling Bai; Li Zhang; Chengwei Liu; Xiaobing Cui; Dan Li; Huazhan Yin (Brain Imaging and Behavior, 2022)

Assessment of water pollution in the Tibetan Plateau with contributions from agricultural and economic sectors: a case study of Lhasa River Basin - Dan Li; Peipei Tian; Donguo Shao; Tiesong Hu; Hongying Luo; Bin Dong; Shahbaz Khan; Yuanlai Cui; Yufeng Luo (Environmental Science and Pollution Research, 2022)

PHD2 attenuates high-glucose-induced blood retinal barrier breakdown in human retinal microvascular endothelial cells by regulating the Hif-1α/VEGF pathway - Jia Li; Xi Lu; Liqing Wei; Dan Ye; Jianqiang Lin; Xiaoyu Tang; Kaixuan Cui; Shanshan Yu; Yue Xu; Xiaoling Liang (Inflammation Research, 2022)

Identification of soybean phosphorous efficiency QTLs and genes using chlorophyll fluorescence parameters through GWAS and RNA-seq - Yuming Yang; Xiuhua Zhu; Ruifan Cui; Ruiyang Wang; Hongyan Li; Jinshe Wang; Huatao Chen; Dan Zhang (Planta, 2021)

Phenolic glycosides and flavonoids with antioxidant and anticancer activities from Desmodium caudatum - Qian-Nan Xu; Dan Zhu; Guang-Hui Wang; Ting Lin; Cui-Ling Sun; Rong Ding; Wen-Jing Tian; Hai-Feng Chen (Natural Product Research, 2021)

MicroRNA-9 inhibits proliferation and progression in retinoblastoma cells by targeting PTEN - Manhai Gao; Zhe Cui; Dan Zhao; Shurong Zhang; Qiang Cai (Genes & Genomics, 2021)

Amygdala-based Functional Network Reveals Dissociated Neural Correlates of Consensual and Idiosyncratic Emotional Movie Experiences - Lin Cui; Bingbing Guo; Dan Zhao; Jiaxin Li; Yu Luo; Ming Meng (Neuroscience Bulletin, 2021)

Phenotype Heterogeneity and Genotype Correlation of MAPT Mutations in a Chinese PUMCH Cohort - Chenhui Mao; Liling Dong; Jie Li; Xinying Huang; Dan Lei; Jie Wang; Shanshan Chu; Caiyan Liu; Bin Peng; Liying Cui; Jing Gao (Journal of Molecular Neuroscience, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Correlation between single-nucleotide polymorphisms and statin-induced myopathy: a mixed-effects model meta-analysis - Qian Xiang; Xiao-Dan Zhang; Guang-Yan Mu; Zhe Wang; Zhi-Yan Liu; Qiu-Fen Xie; Kun Hu; Zhuo Zhang; Ling-Yue Ma; Jie Jiang; Yi-Min Cui (European Journal of Clinical Pharmacology, 2021)

New application of lanthanum-modified bentonite (Phoslock®) for immobilization of arsenic in sediments - Jingzhen Cui; Dan Wang; Juan Lin; Yan Wang; Mingyi Ren; Youwei Yang; Pengling Shi (Environmental Science and Pollution Research, 2021)

Aerosol Measurements by Soot Particle Aerosol Mass Spectrometer: a Review - Yunjiang Zhang; Junfeng Wang; Shijie Cui; Dan Dan Huang; Xinlei Ge (Current Pollution Reports, 2020)

Comparative transcriptome combined with morpho-physiological analyses revealed candidate genes potentially for differential cold tolerance in two contrasting apricot (Prunus armeniaca L.) cultivars - Dan Yu; Xiaojuan Liu; Yifan Cui; Quanxin Bi; Yang Zhao; Dongxing Li; Haiyan Yu; Libing Wang (Trees, 2020)

Genome-wide identification of WD40 genes reveals a functional diversification of COP1-like genes in Rosaceae - Yi-Bo Sun; Xiao-Jia Zhang; Mi-Cai Zhong; Xue Dong; Dong-Mei Yu; Xiao-Dong Jiang; Dan Wang; Wei-Hua Cui; Jiang-Hua Chen; Jin-Yong Hu (Plant Molecular Biology, 2020)

Climate changes in the Lhasa River basin, Tibetan Plateau: irrigation-induced cooling along with a warming trend - Dan Li; Yusi Chen; Tiesong Hu; Yuanlai Cui; Yufeng Luo; Hongying Luo; Qiang Meng (Theoretical and Applied Climatology, 2020)

The nucleic acid positive rate and genotype distribution of human cytomegalovirus in human milk banks in China - Xiaoyu Min; Lin Wang; Aili Cui; Chunli Zhang; Dan Wang; Ying Liu; Zhenghong Li; Wenbo Xu (Archives of Virology, 2020)

Propofol Attenuates α-Synuclein Aggregation and Neuronal Damage in a Mouse Model of Ischemic Stroke - Yuzhu Wang; Dan Tian; Changwei Wei; Victoria Cui; Huan Wang; Yanbing Zhu; Anshi Wu; Yun Yue (Neuroscience Bulletin, 2020)

Effects of shallow groundwater table fluctuations on nitrogen in the groundwater and soil profile in the nearshore vegetable fields of Erhai Lake, southwest China - Dan Zhang; Maopan Fan; Hongbin Liu; Rong Wang; Jixia Zhao; Yanxian Yang; Rongyang Cui; Anqiang Chen (Journal of Soils and Sediments, 2020)

Preemptive meloxicam achieves a better effect on postoperative pain control and similar tolerance compared with postoperative meloxicam in patients receiving arthroscopic knee surgery - Yanxin Yuan; Dan Cui; Yunhong Zhang (Inflammopharmacology, 2019)

The maximum possible amount of drug in rapidly separating microneedles - Dan Dan Zhu; Xiao Peng Zhang; Chang Bing Shen; Yong Cui; Xin Dong Guo (Drug Delivery and Translational Research, 2019)

QTL analysis and candidate gene identification for plant height in cotton based on an interspecific backcross inbred line population of Gossypium hirsutum × Gossypium barbadense - Jianjiang Ma; Wenfeng Pei; Qifeng Ma; Yanhui Geng; Guoyuan Liu; Ji Liu; Yupeng Cui; Xia Zhang; Man Wu; Xingli Li; Dan Li; XinShan Zang; et al. (Theoretical and Applied Genetics, 2019)

The complete chloroplast genome of Siebold’s magnolia: Magnolia sieboldii (Magnoliaceae), a highly ornamental species with attractive aromatic flowers - Yifan Cui; Chong Li; Yue Zhang; Yuan Liu; Yuyao Wang; Dan Li; Fang K. Du (Conservation Genetics Resources, 2019)

Cloning and Expression Analysis of SiCDPK4, a Gene Related to Heterosis in Foxtail Millet [(Setaria italica (L.) P. Beauv.)] - Dan Liu; Suying Li; Lina Wang; Qiang Li; Yanjiao Cui; Xiaodong Dai; Zilong Zhao; Chao Chen; Junxia Li; Zhengli Liu (Journal of Plant Growth Regulation, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

β2-AR regulates the expression of AKR1B1 in human pancreatic cancer cells and promotes their proliferation via the ERK1/2 pathway - Ming-Bing Xiao; Dan-Dan Jin; Yu-Jie Jiao; Wen-Kai Ni; Jin-Xia Liu; Li-Shuai Qu; Cui-Hua Lu; Run-Zhou Ni; Feng Jiang; Wei-Chang Chen (Molecular Biology Reports, 2018)

Cryo-EM structure reveals cylindrical nucleocapsids from two polydnaviruses - Ji-Hui Cui; Ya-Bin Chen; Ming Li; Qiu-Chen Cai; Li-Dan Zhang; Zi-Yun Lu; Jian-Cheng Li; Qi-Shun Zhu; Gang Ji; Kai-Jun Luo (Archives of Virology, 2018)

Pm61: a recessive gene for resistance to powdery mildew in wheat landrace Xuxusanyuehuang identified by comparative genomics analysis - Huigai Sun; Jinghuang Hu; Wei Song; Dan Qiu; Lei Cui; Peipei Wu; Hongjun Zhang; Hongwei Liu; Li Yang; Yunfeng Qu; Yahui Li; Teng Li; et al. (Theoretical and Applied Genetics, 2018)

Short-term daily forecasting of crop evapotranspiration of rice using public weather forecasts - Dan Li; Junying Chen; Yufeng Luo; Fangping Liu; Hongying Luo; Hengwang Xie; Yuanlai Cui (Paddy and Water Environment, 2018)

Identification and characterization of a novel goose-type and chicken-type lysozyme genes in Chinese rare minnow (Gobiocypris rarus) with potent antimicrobial activity - Yingying Zhang; Hui Yang; Weijia Song; Dan Cui; Lixin Wang (Genes & Genomics, 2018)

Response of groundwater level and surface-water/groundwater interaction to climate variability: Clarence-Moreton Basin, Australia - Tao Cui; Matthias Raiber; Dan Pagendam; Mat Gilfedder; David Rassam (Hydrogeology Journal, 2018)

Evaluating environmental equities of urban forest in terms of cooling services using ETM+ and Google data - Ze Tang; Haifeng Zheng; Zhibin Ren; Dan Zhang; Peijiang Wang; Chang Zhai; Mingxing Cui; Xingyuan He (Journal of the Indian Society of Remote Sensing, 2018)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Multi-feature sea–land segmentation based on pixel-wise learning for optical remote-sensing imagery - Dan Wang; Xinrui Cui; Fengying Xie; Zhiguo Jiang; Zhenwei Shi (International Journal of Remote Sensing, 2017)

The Interaction of Mitochondrial Biogenesis and Fission/Fusion Mediated by PGC-1α Regulates Rotenone-Induced Dopaminergic Neurotoxicity - Kaige Peng; Likui Yang; Jian Wang; Feng Ye; Guorong Dan; Yuanpeng Zhao; Ying Cai; Zhihong Cui; Lin Ao; Jinyi Liu; Zhongmin Zou; Yan Sai; et al. (Molecular Neurobiology, 2017)

Low diversity, activity, and density of transposable elements in five avian genomes - Bo Gao; Saisai Wang; Yali Wang; Dan Shen; Songlei Xue; Cai Chen; Hengmi Cui; Chengyi Song (Functional & Integrative Genomics, 2017)

A Novel Segmentation Approach for Intravascular Ultrasound Images - Jiayong Yan; Dan Lv; Yaoyao Cui (Journal of Medical and Biological Engineering, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Effects of selenite and selenate application on distribution and transformation of selenium fractions in soil and its bioavailability for wheat (Triticum aestivum L.) - Fayaz Ali; Qin Peng; Dan Wang; Zewei Cui; Jie Huang; Dongdong Fu; Dongli Liang (Environmental Science and Pollution Research, 2017)

Dynamic expression analysis of early response genes induced by potato virus Y in PVY-resistant Nicotiana tabacum - Shuai Chen; Fengxia Li; Dan Liu; Caihong Jiang; Lijie Cui; Lili Shen; Guanshan Liu; Aiguo Yang (Plant Cell Reports, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Voluntary exercise rescues sevoflurane-induced memory impairment in aged male mice - Dan Tian; Miao Tian; Zhiming Ma; Leilei Zhang; Yunfeng Cui; Jinlong Li (Experimental Brain Research, 2016)

Characteristics of the surface mixed layer depths in the northern South China Sea in spring - Chunhua Qiu; Yongsheng Cui; Jie Ren; Qiang Wang; Dan Huo; Jiaxue Wu; Huan Liu; Huabin Mao (Journal of Oceanography, 2016)

Synthesis and Application of Modified Zero-Valent Iron Nanoparticles for Removal of Hexavalent Chromium from Wastewater - Dan-Lian Huang; Guo-Min Chen; Guang-Ming Zeng; Piao Xu; Ming Yan; Cui Lai; Chen Zhang; Ning-Jie Li; Min Cheng; Xiao-Xiao He; Yan He (Water, Air, & Soil Pollution, 2015)

Induction of forkhead box M1 (FoxM1) by EGF through ERK signaling pathway promotes trophoblast cell invasion - Yunpeng Xie; Dan Cui; Linlin Sui; Yuefei Xu; Ningning Zhang; Yanni Ma; Yinghua Li; Ying Kong (Cell and Tissue Research, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

Effect of quinoid redox mediators on the aerobic decolorization of azo dyes by cells and cell extracts from Escherichia coli - Daizong Cui; Guofang Li; Dan Zhao; Min Zhao (Environmental Science and Pollution Research, 2015)

Application of molecularly imprinted polymers in wastewater treatment: a review - Dan-Lian Huang; Rong-Zhong Wang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Piao Xu; Bing-An Lu; Juan-Juan Xu; Cong Wang; Chao Huang (Environmental Science and Pollution Research, 2015)

Biotransformation of 1,3-propanediol cyclic sulfate and its derivatives to diols by Rhodococcus sp. - Yu-Cai He; Zhi-Cheng Tao; Dan-Ping Zhang; Zhen-Xing Yang; Shan Gao; Cui-Luan Ma (Biotechnology Letters, 2015)

Erratum to: Biotransformation of 1,3-propanediol cyclic sulfate and its derivatives to diols by Rhodococcus sp. - Yu-Cai He; Zhi-Cheng Tao; Dan-Ping Zhang; Zhen-Xing Yang; Shan Gao; Cui-Luan Ma (Biotechnology Letters, 2014)

Characterizing the heavy metal-complexing potential of fluorescent water-extractable organic matter from composted municipal solid wastes using fluorescence excitation–emission matrix spectra coupled with parallel factor analysis - Xiao-Song He; Bei-Dou Xi; Hong-Wei Pan; Xiang Li; Dan Li; Dong-Yu Cui; Wen-Bin Tang; Ying Yuan (Environmental Science and Pollution Research, 2014)

Influence of the composition and removal characteristics of organic matter on heavy metal distribution in compost leachates - Xiao-Song He; Bei-Dou Xi; Dan Li; Xu-Jing Guo; Dong-Yu Cui; Hong-Wei Pan; Yan Ma (Environmental Science and Pollution Research, 2014)

Damming of large river by debris flow: Dynamic process and particle composition - Cui Du; Ling-kan Yao; Subhashsagar Shakya; Lun-gui Li; Xiao-dan Sun (Journal of Mountain Science, 2014)

Effect of BRAF V600E mutation on tumor response of anti-EGFR monoclonal antibodies for first-line metastatic colorectal cancer treatment: a meta-analysis of randomized studies - Dandan Cui; Dan Cao; Yu Yang; Meng Qiu; Ying Huang; Cheng Yi (Molecular Biology Reports, 2014)

Generation of GGTA1 biallelic knockout pigs via zinc-finger nucleases and somatic cell nuclear transfer - Lei Bao; HaiDe Chen; UiMyong Jong; CholHo Rim; WenLing Li; XiJuan Lin; Dan Zhang; Qiong Luo; Chun Cui; HeFeng Huang; Yan Zhang; Lei Xiao; et al. (Science China Life Sciences, 2014)

Characterization of Edenia gomezpompae Isolated from a Patient with Keratitis - Yan Cui; Hui Jia; Dan He; Huimei Yu; Song Gao; Koji Yokoyama; Jing Li; Li Wang (Mycopathologia, 2013)

Verapamil reverses cardiac iron overload in streptozocin-induced diabetic rats - Hong-li Shan; Yan Wang; Jian-wei Wu; Peng-zhou Hang; Xin Li; Li-hua Sun; Jian-cui Qi; Yu-ying Mao; Zhi-dan Sun; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Sorption isotherms and kinetics of Sb(V) on several Chinese soils with different physicochemical properties - Jian-Xin Fan; Yu-Jun Wang; Xiao-Dan Cui; Dong-Mei Zhou (Journal of Soils and Sediments, 2013)

Erratum to: Enhanced degradation of azo dye alizarin yellow R in a combined process of iron–carbon microelectrolysis and aerobic bio-contact oxidation - Bin Liang; Qian Yao; Haoyi Cheng; Shuhong Gao; Fanying Kong; Dan Cui; Yuqi Guo; Nanqi Ren; Duu-Jong Lee; Aijie Wang (Environmental Science and Pollution Research, 2013)

Nonstructural protein-1 of respiratory syncytial virus regulates HOX gene expression through interacting with histone - Yu-rong Tan; Dan Peng; Cui-mei Chen; Xiao-qun Qin (Molecular Biology Reports, 2013)

Functional recombinant human anti-HBV antibody expressed in milk of transgenic mice - Ran Zhang; Dan Cui; Hong Wang; Chuan Li; Xin Yao; Yaofeng Zhao; Mifang Liang; Ning Li (Transgenic Research, 2012)

Enhanced degradation of azo dye alizarin yellow R in a combined process of iron–carbon microelectrolysis and aerobic bio-contact oxidation - Bin Liang; Qian Yao; Haoyi Cheng; Shuhong Gao; Fanying Kong; Dan Cui; Yuqi Guo; Nanqi Ren; Aijie Wang (Environmental Science and Pollution Research, 2012)

MDM2 SNP309 polymorphism and breast cancer risk: a meta-analysis - Erjiang Zhao; Dan Cui; Ling Yuan; Weiquan Lu (Molecular Biology Reports, 2012)

Identification of single nucleotide polymorphisms and haplotypes associated with yield and yield components in soybean (Glycine max) landraces across multiple environments - Derong Hao; Hao Cheng; Zhitong Yin; Shiyou Cui; Dan Zhang; Hui Wang; Deyue Yu (Theoretical and Applied Genetics, 2012)

Effects of SKF-96365, a TRPC inhibitor, on melittin-induced inward current and intracellular Ca2+ rise in primary sensory cells - Jing Ding; Yong Xiao; Dan Lu; Yi-Ru Du; Xiu-Yu Cui; Jun Chen (Neuroscience Bulletin, 2011)

Up-regulation of mitochondrial antioxidation signals in ovarian cancer cells with aggressive biologic behavior - Yue Wang; Li Dong; Heng Cui; Dan-hua Shen; Ying Wang; Xiao-hong Chang; Tian-yun Fu; Xue Ye; Yuan-yang Yao (Journal of Zhejiang University-SCIENCE B, 2011)

Predominance of Precipitation and Temperature Controls on Ecosystem CO2 Exchange in Zoige Alpine Wetlands of Southwest China - Yan Bin Hao; Xiao Yong Cui; Yan Fen Wang; Xu Rong Mei; Xiao Ming Kang; Ning Wu; Peng Luo; Dan Zhu (Wetlands, 2011)

Study on high-temperature-resistant and high-yield Laminaria variety “Rongfu” - Jing Zhang; Yan Liu; Dan Yu; Hongze Song; Jingjin Cui; Tao Liu (Journal of Applied Phycology, 2011)

Inhibition of lung metastasis in mice by intravascular injection of dendritic cells and natural killer cells - Hui-fang Lv; Feng Cui; Chang-hua Yu; Li-li Deng; Jing-jing Ji; Dan Lu; Yu Yang; Wen-xiu Wang; Yu-qing Xu (Biotechnology Letters, 2009)

Detection of quantitative trait loci for phosphorus deficiency tolerance at soybean seedling stage - Dan Zhang; Hao Cheng; Leiyue Geng; Guizhen Kan; Shiyou Cui; Qingchang Meng; Junyi Gai; Deyue Yu (Euphytica, 2009)

Advanced primary peritoneal carcinoma: clinicopathological and prognostic factor analyses - Chao Zhang; Xiao-ping Li; Heng Cui; Dan-hua Shen; Li-hui Wei (Journal of Zhejiang University-SCIENCE B, 2008)

Characterization of impurities in the bulk drug lisinopril by liquid chromatography/ion trap spectrometry - Pei-xi Zhu; Dan-hua Wang; Cui-rong Sun; Zhi-quan Shen (Journal of Zhejiang University-SCIENCE B, 2008)

Combining gene expression QTL mapping and phenotypic spectrum analysis to uncover gene regulatory relationships - Lei Bao; Lai Wei; Jeremy L. Peirce; Ramin Homayouni; Hongqiang Li; Mi Zhou; Hao Chen; Lu Lu; Robert W. Williams; Lawrence M. Pfeffer; Dan Goldowitz; Yan Cui (Mammalian Genome, 2006)

Characterization of a novel impurity in bulk drug of lisinopril by multidimensional NMR technique - Dan-hua Wang; Sai-feng Pei; Ming-hua Zhou; Cui-rong Sun; Yuan-jiang Pan (Journal of Zhejiang University-SCIENCE B, 2006)